Successful Point-Of-Care Ultrasound-Guided Treatment of Submassive Pulmonary Embolism - Myers, Samantha J. (Clin Pract Cases Emerg Med, 2017)
Pulmonary embolism is associated with significant mortality and impaired long-term functional outcomes. Timely identification and treatment is crucial for successful management. Unfortunately, prompt diagnosis can be challenging in patients without overt signs of cardiovascular compromise. Point-of-care cardiac ultrasound (POCCUS) can be used to identify signs of acute pulmonary embolism, risk stratify patients for adverse outcomes and assess response to therapy. This report describes a patient with submassive pulmonary embolism and evidence of acute right ventricular strain on POCCUS successfully treated with thrombolytic therapy. The dynamic changes observed on point-of-care ultrasound are presented.